Quem é esse brincante? história social do Bumba-meu-boi e ensino de história - FERREIRA, Daniel Wollace Marques (2023)
The present study aims to discuss the construction of African History and the presence of black personalities in History teaching in the final years. The hypothesis that intertwines this work is that there is still an extensive absence of black characters and deeper cultural and social discussions in teaching, making the applicability of Law 10.639/2003 unfeasible, which registers the mandatory teaching of Afro-Brazilian and African History and Culture and the National Curricular Guidelines for the Education of Ethnic-Racial Relations. To carry out this research, the methodology used was bibliographic, identifying that this process begins even in the construction of the first school curricula extending to the present day. The exploratory research was essential for the construction of the didactic product "Activity Booklet" offered at the end of this work, such product intends to rescue the memory of black characters linked to the history of Bumba-meu-boi of Maranhão. This festivity, which is currently considered the biggest popular party in the state, is the starting point that allowed the reconstruction of the stories of black characters connected to this popular festivity, and that have little prestige in local history teaching. In addition, Heritage Education was established as a teaching bias, scrutinizing the possibilities that this teaching tool allows for fixing the stories and memories of these personalities. We believe that the adoption of such measures is essential for the promotion of ethno-racial education, both for the valorization and the recognition of the importance of including the stories of these characters. Finally, works such as these allow the deconstruction of racist discourses and practices in basic education, establishing critical views about the history and culture of these subjects.